Counting the homeless in Papua New Guinea 2024 population and housing census - IGE, Olugbenga A; Amosun, Peter A; Lotu, Logo (Interdisciplinary journal of rural and community studies, 2023)
The 2011 population census in Papua New Guinea (PNG) failed to generate reliable data due to logistical constraints and inadequate capacity. Addressing this, this conceptual communication analyses the benefits of using single contact census, capture-recapture method, and indirect estimation to enumerate the homeless population in the PNG 2024 Census. The study argues that, owing to the distinct geographical distribution of the homeless in urban locales, the single-contact census and the capture-recapture method emerge as the most suitable strategies for the 2024 enumeration. The exploration meticulously outlines the practical assumptions imperative for deploying these techniques, emphasizing their pivotal role in ensuring an accurate representation of the homeless demographic. This paper serves as a pivotal guide to adapting and refining enumeration methodologies to overcome challenges witnessed in the previous PNG census. The study concludes by explaining the practical assumptions for using the single-contact census and the capture-recapture method in the PNG 2024 census.